The evolution of restaurants and bars in Vieux-Québec since 1900 - Gazillo, Stephen (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1981)
This paper describes the salient features of the evolution of restaurants and bars in Vieux-Québec since 1900. Their spatial distribution has led to the creation of three distinct sectors within the historic district. The paper also focuses on how two different cultures, popular culture and "élite culture", are identifiable in the way proprietors describe their establishments.